Benign multicystic peritoneal mesothelioma occurring in bilateral inguinal canals metachronously: a case report - Hiroyuki Oshikiri; Yohei Ozawa; On Suzuki; Masahiro Usuda; Go Miyata (Surgical Case Reports, 2022)
Abstract Background Benign multicystic peritoneal mesothelioma (BMPM) is a benign tumor that usually occurs in middle-aged females. Although several published studies have reported the occurrence of this tumor in the abdominal cavity, few have documented its development in the inguinal region. Case presentation We present a case of a 48-year-old female presenting with a bulge in her left inguinal region. Physical examination revealed a golf ball-sized nodule in the left inguinal region that could not be pushed back into the abdominal cavity. Contrast-enhanced computed tomography showed a multicystic tumor; therefore, the patient was diagnosed with inguinal hernia or hydrocele of the Nuck’s canal. We performed surgical resection and hernia repair using the mesh plug method. The resected specimen was 80 mm in length and contained a multicystic tumor. Pathological examination showed that the cyst wall was lined by a single layer of cuboidal to single layer squamous epithelium. Immunohistochemistry revealed positivity for calretinin in the epithelial cells, for which a diagnosis of BMPM was established. The patient returned to our hospital after 5 years with symptoms similar to the previous episode, but this time in the right inguinal region. Imaging studies showed a tumor in the right inguinal region with the same characteristics as the previous one. The patient underwent tumor resection and hernia repair using the same technique. The resected tumor was 45 mm in length and had characteristics similar to the previously resected tumor. The presence of calretinin and D2-40 on immunohistochemistry led to the diagnosis of BMPM. There was no recurrence of BMPM for 33 months after the secondary surgery. Conclusions Here we present the first report of metachronous BMPM occurring in bilateral inguinal canals. Although the pathogenesis of BMPM remains unclear, reactive changes have been suggested to cause tumors originating from the groin. The treatment of choice for BMPM is surgical resection. For diagnosis, pathological examination with immunostaining can be useful. The most appropriate postoperative follow-up for inguinal BMPM is controversial, and the accumulation of more inguinal BMPM cases is needed.